Impact of focused wave groups on pier structures: a case study of severe breaking waves at Pont del Petroli during storm Gloria - Altomare, Corrado; Gironella, Xavier; Marzeddu, Andrea; Viñes Recasens, Manuel; Mösso, Cesar; Sospedra, Joaquim (Frontiers in Built Environment, 2024)
In January 2020, the footbridge connecting the seaward platform of the Pont del Petroli pier to Badalona beach collapsed due to the severe sea storm named Gloria. Approximately 15 m of the footbridge fell into the sea as a result of prolonged wave action and strong impacts. To understand the complex interaction between waves and structures that led to the pier’s collapse during the storm, a composite modelling approach was developed. The loads on each pier element were initially evaluated using the meshless DualSPHysics code, which employs the Smoothed Particle Hydrodynamics (SPH) method. This evaluation was conducted under severe wave conditions analogous to those experienced during the storm. Numerical models informed the design of an experimental campaign carried out at the Maritime Engineering Laboratory of Universitat Politècnica de Catalunya—BarcelonaTech, using the CIEM large-scale wave flume facility in Barcelona, Spain. Post-storm bathymetric surveys revealed significant alterations in the seabed profile near the affected infrastructure, including sediment deposition and a reduction in water depth from 10 m to 8 m. Consequently, it was anticipated that wave transformation and breaking in the vicinity of the structure would be substantially affected. To explore this phenomenon, various extreme wave impacts were experimentally simulated using focused wave groups. The physical model findings unveiled the forces that the pier endured during the storm Gloria. The results indicate that wave phases influence individual waves, with waves that are biased and asymmetric experiencing higher peaks than those focused on the crest. This insight helps to explain the structural failure of the footbridge during the storm and underscores the importance of considering wave phase impacts in the design and assessment of coastal infrastructure. The combined numerical and experimental approach provides a comprehensive understanding of the forces at play, contributing valuable knowledge to the field of coastal engineering and infrastructure resilience.